Management Audit and Information Technology Governance at Village-Owned Enterprises (BUMDesa) Catu Kwero Sedana Pecatu - I Kadek Budi Sandika; Ni Wayan Eka Wijayanti; Ni Luh Ayu Prima Dania; Putu Adreal Candranatha; I Gede Iwan Sudipa (BIOS: Jurnal Informatika dan Sains, 2025)
BUMDesa Catu Kwero Sedana Pecatu was formed through Pecatu Village Regulation Number 10 of 2014 as a strategic effort to strengthen the local economy. Operations began in 2017 with a waste management business unit, and in 2022 expanded with a trade and services unit. As legality is strengthened (legal entity 2022, NIB 2024), the need for information technology (IT) governance becomes increasingly important to support efficiency, transparency and accountability. However, there has never been an in-depth study of IT readiness, effectiveness, and risk, so an IT management and governance audit is needed. This research uses a descriptive qualitative approach with a case study method at BUMDesa Catu Kwero Sedana Pecatu. Data was obtained through document analysis, interviews, and observations. The evaluation framework refers to COBIT and the maturity model to assess five main aspects: IT policies and procedures, organizational structure and IT HR capabilities, IT maturity level, IT risk identification, and internal control effectiveness. The audit showed that the IT maturity level was at Level 1 - Initial (average score 0.6) with practices that were ad hoc, lacked documentation, and were not integrated. Significant risks were found such as delays in application development, HPP calculation errors due to system limitations, absence of backup policies, dependence on vendors, and potential data privacy violations. Internal controls are still weak in the aspects of system security, data backup, access authorization, and transaction monitoring. Recommendations include the preparation of an IT Master Plan, establishment of a specialized IT unit, HR training, implementation of information security policies, and implementation of an integrated information system aligned with BUMDesa's business strategy.